PERIPARTUM HYSTERECTOMIES - LEADING RISK FACTORS AND CAUSES - Tihomir Totev; Desislava Staneva; Tsvetan Oslekov; Georgi Stamenov (Peytchinski Publishing, 2020)
Purpose: To define the frequency, significant factors and causes that necessitated peripartum hysterectomies. Material and Methods: We studied retrospectively and prospectively 21 patients who underwent peripartum hysterectomies at "Nadezhda" Women's Health Hospital between January 2013 and July 2019. Results: The frequency of peripartum hysterectomy was 1.96/1000 deliveries, and 95 % of them were performed during or after a cesarean birth. The intrapartum ones were carried out mainly because of uterine atony or abnormal insertion of the placenta. The interventions made in the early postoperative period were undertaken in cases of severe pelvic inflammations and postoperative hematomas. Conclusion: Patients undergoing cesarean section are at risk for peripartum haemorrhages, which are associated with many risk factors: previous cesarean section and other interventions such as myomectomy, placenta praevia.